The venous return simulator: an effective tool for investigating the effects of external compression on the venous hemodynamics--first results after thigh compression - Fullana, J M; Cros, F; Becker, F; Ouchene, A; Partsch, H (VASA, 2005)
To present a virtual model, the venous return simulator (VRS), designed to compute venous hemodynamic variations when compression is applied to the leg. The VRS defines a numerical network of the lower extremity and computes the dynamic variables (flow rate, venous diameter and internal pressure) for a defined external pressure. The VRS was based on physiological data from the literature and clinical studies on healthy subjects. Clinical correlations were required to confirm its validity; for this purpose, we carried out experiments simulating the conditions of a clinical trial, in which the diameter of superficial and deep veins was measured while increasing pressures (20, 40 and 60 mmHg.) were applied to the thighs of patients enduring deep valvular insufficiency and venous ulcers. The diameters and flow rates calculated using our VRS model were compared with the experimental data obtained at the same thigh compression levels. The numerical results of VRS are in good agreement with the clinical data obtained by Duplex, (R2 = 0.96). In accordance with the in vivo measurement the computed results show that only a pressure greater than 40 mmHg is able to reduce the venous diameter at thigh-level, both in the great saphenous vein and in the femoral vein. The venous return simulator computes lower limb hemodynamic parameters under static conditions. The good correlation existing between the VRS and the data obtained in a previous clinical study shows that this numerical approach could provide a useful means of predicting the hemodynamic consequences of compression therapy.